PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN (STUDI KASUS DI KSPPS BMT AL-HIKMAH SEMESTA MLONGGO JEPARA) - Lazulfa, Indana; Maulidah Rahmawati, Fitri (Tinta Nusantara 2018 Vol.1, 2025)
This study aims to analyze the influence of transformational leadership on employee performance at KSPPS BMT Al Hikmah Semesta. This study uses a quantitative approach. The variables used in this study are Transformational Leadership (X) and employee performance (Y). The population in this study was all 299 employees at KSPPS BMT Al Hikmah Semesta across 40 branch offices. The sample in this study used saturated sampling, where the entire population was sampled. Data collection used questionnaires and literature review. The data analysis method used in this study was simple linear regression analysis. The results indicate that transformational leadership influences employee performance at KSPPS BMT Al Hikmah Semesta Mlonggo Jepara. This means that the higher the implementation of transformational leadership, the higher the employee performance.